An Exploratory Study of Pharmacists’ and Migrant Workers’ Perspectives toward the Use of a Digital Language Translation Platform - Pattarabovornwut, Kasipat; Damnet, Anamai; Poo-udom, Aunchistha (Research Community and Social Development Journal, 2026)
Introduction: Community pharmacies serve as highly accessible primary healthcare units for both the general public and migrant workers. However, persistent language barriers remain a critical constraint that can compromise the quality of pharmaceutical care. This study aimed to identify communication barriers between migrant workers and pharmacists, assess their awareness of and attitudes toward digital translation platforms, and compare the perspectives of both groups regarding the communication effectiveness and service quality facilitated by these platforms. Methodology: Utilizing a quantitative survey research design, data were gathered from two distinct cohorts: 62 community pharmacists via an online questionnaire, and 30 Myanmar migrant workers via a questionnaire administered with the assistance of an interpreter. Intergroup differences were analyzed using descriptive statistics and evaluated using the Mann–Whitney U test. Results: Both pharmacists and migrant workers indicated that digital translation platforms significantly enhance communication and pharmaceutical service quality. These platforms were found to minimize communication errors, improve comprehension of medication instructions, bolster migrant workers’ perceived safety during consultations, increase convenience, foster trust, and project a positive image for community pharmacies. Furthermore, Mann–Whitney U test analysis revealed that pharmacists held significantly more positive perceptions regarding the platform's capacity to reflect service quality, standards, and readiness compared to the Myanmar migrant workers. Discussion: Digital translation platforms act as vital mechanisms for facilitating intercultural communication within community pharmacies. To bridge critical language gaps linked directly to patient trust and clinical safety, translation software tailored specifically for pharmaceutical contexts should be developed. Future research should expand the cohort to include international tourists to examine language-related limitations across diverse cultural and demographic contexts. Recommendations: The development of a dedicated, pharmacy-specific digital translation platform supporting Myanmar and Cambodian languages is highly recommended. This platform should incorporate a validated, high-accuracy database of clinical and health advice terminology, establish strict safety usage standards, and be paired with intercultural communication training programs for pharmacists.